A racionalidade indutiva: em que consiste? - Ventura, Pedro Paulo Ramos (Universidade do Vale do Rio dos Sinos, 2015)
The general objectof this dissertation is to investigate the nature of inductive reasoning based on the analysis of David Hume about inductive inferences, which depend, for him, on the human ability to establish inferences from principles of human nature. The reasoning concerning the cause and effect notions are founded on experience (and on our natural ability to perceive similarities, contiguity, and being familiarized to what appears to us as a constant conjunction). On the other hand, Stuart Mill develops in his book A System of Logic (1960) - ((1900)), the five methods of induction that would become known as Mill’s Methods. The role of inductive reasoning capacity will be the guideline of this dissertation. This paper aims to examine Stuart Mill’s proposal of inductive rationality, as well asunderstand if the induction is a rational inference, determine what kind of rationality is behind the induction and explain the various inductive inferences that Mill presents, through his examples. The main purpose is to perform a contrast between the distinction that Hume established between ideas, instincts, habits, similarity, contiguity, causality and inference and Mill’s inductive methods.
Keywords: Lógica; Argumentação; Racionalidade; Indução e inferência; Logic; Argumentation; Rationality; Induction and inference; ACCNPQ::Ciências Humanas::Filosofia